Fermatean Picture fuzzy continuity in Fermatean Picture fuzzy topological spaces - B, Maheswari; V, Chitra; S, Jafari (Communications in Mathematics and Applications, 2025)
The purpose of this paper is to define a new Picture fuzzy continuous mapping in Fermatean Picture fuzzy topological spaces and investigate its fundamental properties. In addition, we explore a key topological concept FPF- connectedness within the framework of Fermatean Picture fuzzy topology.